Spices control chickpea pests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Coriander and egrets are helping chickpea farmers in India to control pests that have developed resistance to pesticides. Chickpea leaves and pods naturally exude an acid that usually keeps pests away. Recently. though, the pod borer (Helicoverpa...